Uit archief-Bosch Kemper, map 67, 106. Portret afgedrukt in de Amsterdamse Studenten Almanak van 1861 - Sluyter, D.J.
Uit archief-Bosch Kemper, map 67, 106. Portret afgedrukt in de Amsterdamse Studenten Almanak van 1861.